Therapeutic Interventions against Inflammatory and Angiogenic Mediators in Proliferative Diabetic Retinopathy. (17th September 2012) - Gologorsky, Daniel; Thanos, Aristomenis; Vavvas, Demetrios
Abstract : The global prevalence of diabetes is estimated to be 336 million people, with diabetic complications contributing to significant worldwide morbidity and mortality. Diabetic retinopathy results from cumulative microvascular damage to the retina and inflammation is recognized as a critical driver of this disease process. This paper outlines the pathophysiology leading to proliferative diabetic retinopathy and highlights many of the inflammatory, angiogenic, and cytokine mediators implicated in the development and progression of this disease. We focus a detailed discussion on the current targeted therapeutic interventions used to treat diabetic retinopathy.